2014
DOI: 10.1093/schbul/sbu004
|View full text |Cite
|
Sign up to set email alerts
|

Left-Dominant Temporal-Frontal Hypercoupling in Schizophrenia Patients With Hallucinations During Speech Perception

Abstract: These findings replicate our previous work showing generalized speech-related functional network hypercoupling in schizophrenia during inner verbal thought and SP, but extend them by suggesting that hypercoupling is related to past-week hallucination severity scores during SP only, when control over verbal material is not required. This result opens the possibility that practicing control over inner verbal thought processes may decrease the likelihood or severity of hallucinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 47 publications
5
38
0
Order By: Relevance
“…Our results are in line with functional imaging studies reporting a hypercoupling between frontal and temporal regions in non-psychotic individuals with hallucinations (Diederen et al, 2013) and in AVH + patients with schizophrenia (Lavigne et al, 2015). The WM alterations observed in patients with predominantly negative symptoms could be linked to a high susceptibility of WM tracts to inflammatory mediators in this population (Alba-Ferrara and de Erausquin, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with functional imaging studies reporting a hypercoupling between frontal and temporal regions in non-psychotic individuals with hallucinations (Diederen et al, 2013) and in AVH + patients with schizophrenia (Lavigne et al, 2015). The WM alterations observed in patients with predominantly negative symptoms could be linked to a high susceptibility of WM tracts to inflammatory mediators in this population (Alba-Ferrara and de Erausquin, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…shown to be favored at the cell and tissue level by FH interaction with polyanions such as glycosaminoglycans on mammalian cell surfaces (39,43). Thus, to study the effect of FH on C3 proconvertase and C3 convertase formation in conditions mimicking FH interaction with cell surfaces, we performed C3bB(Ni 2ϩ ) and C3bBb(Ni 2ϩ ) formation assays using wells coated with mixtures of C3b and HS (3 or 30 g/ml, Fig.…”
Section: Effect Of Fh On C3bb(ni 2ϩ ) C3 Proconvertase and C3bbb(ni 2mentioning
confidence: 99%
“…Thus, a clear pattern of increased interaction among the auditory-language and striatal brain regions occurs while patients hallucinate. This finding could explain why AVH are such realistic experiences of speech: increased coordinated activity in this circuitry has been observed during speech perception relative to inner verbal thought (Lavigne et al, 2015). However, the number of symptom capture studies is still low, and more data are needed in this regard.…”
Section: Discussionmentioning
confidence: 88%
“…However, using speech perception, and comparing AVH and NoAVHs patients, another study found increased coordinated activity in the STG and dACC/SMA (Lavigne et al, 2015). The importance of the co-activation of the STG and the dACC/SMA parallels the RS work, and observation of a disconnection is apparently more frequent in the task-based than in the resting-state studies.…”
Section: Functional Connectivity Studiesmentioning
confidence: 99%